Ḵẖut̤bāt-i ʻāliyah : yaʻnī, Āl Inḍiyā Muslim Ejūkeshnal Kānfarans, ʻAlīgaṛh ke cahal sālah ḵẖut̤bāt kā majmūʻah - Zubairī, Anvār Aḥmad (SAMP early 20th-century Indian books project, 1927)
Text of forty presidential addresses, chiefly on Muslim education in India delivered during the forty years of Muslim Educational Conference.